Depolymerization of technical-grade polyamide 66 and polyurethane materials through hydrogenation - Zhou, Wei; Neumann, Paul; Batal, Mona Al; Rominger, Frank; Hashmi, A. Stephen K.; Schaub, Thomas (ChemSusChem, 2020)
Chemical recycling provides a promising solution to utilize plastic waste. Here, a catalytic hydrogenative depolymerization of polyamide 66 (PA 66) and polyurethane (PU) was developed. The system employed Ru pincer complexes at high temperature (200 °C) in THF solution, and even technical-grade polymers could be hydrogenated with satisfactory yields under these conditions. A comparison of the system with some known heterogeneous catalysts as well as catalyst poisoning tests supported the homogeneity of the system. These results demonstrate the potential of chemical recycling to regain building blocks for polymers and will be interesting for the further development of polymer hydrogenation.
Gesehen am 07.10.2021